2002
DOI: 10.1128/cdli.9.4.840-845.2002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Urine as a Clinical Specimen for Diagnosis of Hepatitis A

Abstract: The present study pertains to the evaluation of urine as a specimen for detection of anti-hepatitis A virus (anti-HAV) antibodies. Immunoglobulin M (IgM), IgG, and IgA capture enzyme-linked immunosorbent assays for hepatitis A were performed on paired serum and urine specimens collected from hepatitis A patients (n ‫؍‬ 92), healthy individuals (n ‫؍‬ 100), non-A hepatitis patients (n ‫؍‬ 70), and patients with nonhepatic diseases (n ‫؍‬ 64, including 37 renal disease patients). Hepatitis A patients seropositiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
(20 reference statements)
1
15
1
2
Order By: Relevance
“…The most striking feature in this patient was significantly high anti-HAV IgG titers as compared to that of the hepatitis A patients without the syndrome of present study and that reported previously [Joshi et al, 2002]. This may be indicative of clinical severity of HAV infection [Sata et al, 1996].…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The most striking feature in this patient was significantly high anti-HAV IgG titers as compared to that of the hepatitis A patients without the syndrome of present study and that reported previously [Joshi et al, 2002]. This may be indicative of clinical severity of HAV infection [Sata et al, 1996].…”
Section: Discussionmentioning
confidence: 46%
“…Anti-HAV IgG and IgA were detected in all serum samples by IgG and IgA capture ELISA [Joshi et al, 2002]. An IgM capture ELISA employed for the detection of recent infection with HAV validated at National Institute of Virology, Pune was found comparable to that of commercially available immunoassay from Abbott Laboratories (Chicago, IL) in its sensitivity and specificity [Chitambar et al, 1994].…”
Section: Serological Findingsmentioning
confidence: 99%
“…Diagnosis of other viral infections in urine and saliva samples has been reported for human immunodeficiency virus (HIV), Hepatitis A, B, and C, and rubella [14][15][16][17][18][19][20], and more recently in other flaviviruses, West-Nile virus (WNV) [21][22][23] and Dengue (DENV) serotypes -1, -2, -3, and -4 [24][25][26][27][28][29][30][31][32][33][34][35]. WNV can be detected longer in urine than serum [21] and can be isolated from urine [22,23].…”
Section: Advantages Of Non-invasive Sample Collectionsmentioning
confidence: 99%
“…IgG and IgA anti-HAV are detected in serum, saliva, urine, and feces (39,60,115,123,151,152,177,178,183,214). Saliva tests have been reported as an alternative to conventional serum testing for anti-HAV due to their simplicity of sample collection (115,177,178).…”
Section: Pathogenesis and Natural History Of Hav Infectionmentioning
confidence: 99%